2012
DOI: 10.1096/fj.12-211730
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 is a novel regulator of angiogenesis in human breast cancer

Abstract: Lipocalin 2 (Lcn2), a member of the lipocalin family, is up-regulated in a variety of epithelial cancers. We have previously reported that Lcn2 induces the epithelial to mesenchymal transition in breast cancer through the estrogen receptor α/Slug axis and that it is a potential noninvasive biomarker of this disease. Here, we report the novel finding that Lcn2 regulates breast cancer angiogenesis. Vascular endothelial growth factor (VEGF), a key angiogenic activator, was significantly increased with Lcn2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 28 publications
3
115
2
Order By: Relevance
“…Endometriosis, such as tumorigenesis, requires angiogenesis for the ectopic mass to expand (Vargha et al 2008). As Yang's report mentioned, LCN2 may regulate angiogenesis in human breast cancer, although LCN2 levels merely correlated with vessel formation and tumor growth in breast cancer cells (Yang et al 2013). The finding supports a relationship between LCN2 and angiogenesis during the growth of endometrial tissue within the peritoneum.…”
Section: Discussionmentioning
confidence: 82%
“…Endometriosis, such as tumorigenesis, requires angiogenesis for the ectopic mass to expand (Vargha et al 2008). As Yang's report mentioned, LCN2 may regulate angiogenesis in human breast cancer, although LCN2 levels merely correlated with vessel formation and tumor growth in breast cancer cells (Yang et al 2013). The finding supports a relationship between LCN2 and angiogenesis during the growth of endometrial tissue within the peritoneum.…”
Section: Discussionmentioning
confidence: 82%
“…In this sense LCN2, a newly identified biomarker and a potential therapeutic target for breast cancer, and the possible mechanisms underlying its role in tumorigenesis and metastasis as reported by Xiaohong et al (2011);Yang et al (2013).…”
Section: Effect Of Nucks-1 Overexpression On Cytokines Profilingmentioning
confidence: 90%
“…Furthermore, their contributions to the tumor angiogenesis have been reported (Salgado et al, 2002;Yang et al, 2013). Moreover, it has been shown that treatment effectiveness and prognosis of cancer are determined by disease stage and activity of the immune system modulated by different interleukins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The excessive expression of VEGF has a close relationship with the growth, invasion and metastasis. A variety of experiment in vitro demonstrated that the growth factor, eg., bFGF, TGF-β1 and PDGF are able to enhance the expression and activate the capability of angiogenesis (Kasuya et al, 2011;Yang et al, 2012). The increasing of vascular density presents the accelerated speed of tumor, which could promote the metastasis of cancer.…”
Section: Discussionmentioning
confidence: 99%